The physics and chemist parametric in Labuan Terata Waters, Sumbawa at transitions season - Neri Kautsari; Yudi Ahdiansyah (Jurnal Perikanan dan Kelautan, 2015)
Labuhan Terata Waters, Sumbawa, West Nusa Tenggara is one of the waters are very important for Labuhan Terata peoples because function for fisheries, but asses water quality especially transitions season is minus. The research objective was to assess physics and chemist parametric in the Labuhan Terata waters at transitions season. Oceanographic research in the Labuhan Terata waters have been carried out in May to June 2015. Current, brightness, temperature, dissolved oxygen (O2), acidity (pH), salinity, phosphate and nitrate parameters was measured directly from a layer surface at five research stations. The degree of temperature was measured thermometer Hg, acidity (pH) was measured with pH meter, dissolved oxygen was measured dissolved oxygen meter (DO meters), measurement of nutrients (phosphate and nitrate) concentration used spectrophotometry method. Result of the analysis showed that Labuhan Terata waters has current range from 0.39–0.93 m.dt-1, temperature of 28.50–30.00 °C, brightness 4.00–6.55 m, salinity of 30.50–31.33 psu, dissolved oxygen of 10.40-12.83 mg.L-1, pH of 8.04 – 8.70, phosphate of 0.05 – 0.75 mg.L-1 and nitrate 2.83 – 4.50 mg.L-1.